Analysis of Inverter Drive Working System as 3-Phase AC Motor Rotation Speed Regulator - Prido Singarimbun; Siti Anisah; Hamdani Hamdani (Budapest International Research in Exact Sciences (BirEx) Journal, 2022)
The use of induction motors in industry and factories is more profitable than DC or synchronous motors, one of the advantages is easy maintenance and high efficiency. On machines in the industry speed regulation is necessary. Along with the development of power electronics, this has become very easy to do, namely by supplying the motor with a variable speed drive (VSD) inverter. With a variable speed drive inverter supply, it is possible to adjust the motor speed by adjusting the voltage frequency. This study was conducted to determine the effect of variable frequency by using a variable speed drive inverter on the performance of a three-phase induction motor. Tests were conducted at frequencies of 5, 10, 15, 20, 25, 30, 35, 40, 45, and 50 Hz (inverter frequency) and the motor was loaded with 0.5Nm. From the study, it was concluded that, among other things, the use of a variable speed drive inverter resulted in greater motor losses and the motor produced a louder sound. At the same frequency (50 Hz) the motor efficiency is better when supplied directly from the power grid.